Pierwszy Kodeks Cywilny Chińskiej Republiki Ludowej - Kania, Małgorzata (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
The article “First Civil Code of the People’s Republic of China” describes short history of rounds of work on civil code’s drafts from the establishment of People’s Republic in China in 1949, the goal implementation, as well as the structure of adopted on May 28th, 2020 Civil Code of People’s Republic of China and content of its seven books: Book One General Part, Book Two Real Rights, Book Three Contracts, Book Four Personality Rights, Book Five Marriage and Family, Book Six Succession, Book Seven Tort Liability.
Keywords: China; People's Republic of China; Civil Code of the People's Republic of China; civil code in China; civil law in China